2015
DOI: 10.1016/j.surg.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the determinants of patient satisfaction with surgical care using the Consumer Assessment of Healthcare Providers and Systems surgical care survey (S-CAHPS)

Abstract: Background Patient satisfaction has been increasingly emphasized, including the use of financial penalties for underperformance. However current measures of patient satisfaction do not address aspects specific to the care of surgical patients. We therefore aimed to examine the recently validated Surgical Care Survey (S-CAHPS) in order to determine which aspects of perioperative care are predictive of satisfaction with the surgeon. Methods All patients undergoing a general surgery operation at our institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 21 publications
1
46
0
1
Order By: Relevance
“…For pediatric trainees, there is inherent complexity around effective communication with patients and families (21). Communication skills' training for medical students has gained more focus recently (22), particularly in surgical specialties such as Obstetrics and Gynecology (23) and General Surgery (24), which may have some role in our study ndings.…”
Section: Discussionmentioning
confidence: 99%
“…For pediatric trainees, there is inherent complexity around effective communication with patients and families (21). Communication skills' training for medical students has gained more focus recently (22), particularly in surgical specialties such as Obstetrics and Gynecology (23) and General Surgery (24), which may have some role in our study ndings.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the simple affirmation that weather continues to contribute to pain after fracture healing can greatly relieve patient stress and encourage patients to believe they are recovering appropriately rather than experiencing a poor outcome. Furthermore, as patient generated quality metrics such as the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey are increasingly tied to hospital ratings and reimbursement, adequate counseling is ever more important [37][38][39]. Schmocker et al found that communication was the surgeonrelated characteristic most predictive of high post-operative HCAHPS scores [39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as patient generated quality metrics such as the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey are increasingly tied to hospital ratings and reimbursement, adequate counseling is ever more important [37][38][39]. Schmocker et al found that communication was the surgeonrelated characteristic most predictive of high post-operative HCAHPS scores [39]. Informing patients that they may experience variations in pain related to weather conditions one year or greater after orthopaedic trauma is an important aspect of physicianpatient communication.…”
Section: Discussionmentioning
confidence: 99%
“…Quality ratings were categorized into ratings of 9 or 10, versus ratings below 9 for analyses, similar to previous analyses of CAHPS surveys [20,21]. We also performed a sensitivity analysis with different cutoffs including 10 versus 0-9, and 8-10 versus 0-7 [22].…”
Section: Statistical Analysesmentioning
confidence: 99%